MENGENAL LEBIH DEKAT ANALISIS PASAR MODAL PERSPEKTIF SYARI`AH - Iskandar Budiman (Jurnal Investasi Islam, 2016)
The development of Sharia capital market system in Indonesia based on sharia economic values which controlled by Indonesian Capital Market Architecture to provide an alternative sharia finance product for Indonesian people. Synergically, the sharia capital market system moving widely to support society’s financial mobilization for increasing financial capability for national economic growth. The characteristic of Sharia capital market system by using profite contribution and loss sharing mechanism gives more profitable for both capitalist and someone who is doing business. There is also put forward justification values in transactions, ethically invest, put forward togetherness and brotherhood values in production but also avoid all speculative acts in some financial transactions. Providing various contracts and market services with variety of financial schemes, the sharia capital market becomes an alternative credible stock-exchange growth and it can be enjoyed by all levels of moslim`s capitalist. In the context of macro economic system, widely used various products and sharia financial instruments, it can tighten financial in real sectors of business development. The goal of Islamic capital market are providing instruments for supporting financial acts and business activities. Exactly, it decreases speculative transactions, so that it supports wholly financial system stability and provides significant contribution for harmony life. As a result, the society responds positively toward the products and services provided by the management of sharia capital market to increase society’s economy. It can fasten the process of empowering society’s economy which gives positive contribution in understanding business starting with small capital. As a matter of fact, the development of sharia capital market system needs more supports from moslem`s society, stated under regulation and it would be controlled by authorized person (National Sharia Boards/Dewan Syariah Nasional).